Geographic information science : 8th International Conference, GIScience 2014, Vienna, Austria, September 24-26, 2014. Proceedings - Pebesma, Edzer; Stewart, Kathleen; Frank, Andrew U.; Duckham, Matt (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Geographic Information Science, GIScience 2014, held in Vienna, Austria in September 2014. The 23 full papers presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections such as information visualization, spatial analysis, user-generated content, semantic models, wayfinding and navigation, spatial algorithms, and spatial relations.